Transnational Municipal Networks as a Mechanism for Marine Governance Toward Climate Change Adaptation and Mitigation: Between Potential and Practice - Dumała, Hanna; Łuszczuk, Michał; Piwowarczyk, Joanna; Zieliński, Tymon (Frontiers in Marine Science, 2021)
Many municipalities undertake actions individually and/or collectively, in cooperation with central administrations, regional authorities, the private sector, and other municipalities (both nationally and internationally). This paper aims to examine how they use Transnational Municipal Networks (TMNs) as a tool for cooperation that supports marine governance in the context of climate change adaptation and mitigation. The analysis is carried out at two dimensions: spatial range (global or regional) and spatial identity (coastal or inland). Three case studies of TMNs are examined in detail: the C40 Cities Climate Leadership Group (C40); Connecting Delta Cities (CDC) and the Union of Baltic Cities (UBC). As research has shown, due to their organizational and normative limitations and a lack of maturity in ocean literacy, TMNs are not able to fully engage in all the activities related to climate change adaptation and mitigation as suggested by the UNEP. The TMNs implement both mitigation and adaptation measures, although ʽsoft’ mitigation actions seem to be the most common. While the scale and innovativeness of a networks’ operation are determined by their specificity resulting from their spatial identity, the effectiveness of jointly developed strategies and actions depend heavily on the allocation of human resources and the level of commitment of the involved cities toward becoming leaders.